Korean Red Ginseng Suppresses Metastasis of Human Hepatoma SK-Hep1 Cells by Inhibiting Matrix Metalloproteinase-2/-9 and Urokinase Plasminogen Activator - Ho, Yu-Ling (Hindawi Publishing Corporation, 2012)
Korean red ginseng and ginsenosides have been claimed to possess wide spectrum of medicinal effects, of which anticancer effect is one. The present study was undertaken to investigate the antimetastatic effect of Korean red ginseng on human hepatoma as well as possible mechanisms. The inhibitory effect of the water extract of Korean red ginseng (WKRG) on the invasion and motility of SK-Hep1 cells was evaluated by the Boyden chamber assay in vitro. Without causing cytotoxicity, WKRG exerted a dose-dependent inhibitory effect on the invasion and motility, but not adhesion, of highly metastatic SK-Hep1 cells. Zymography analyses revealed significant downregulating effects on MMP-2, MMP-9, and uPA activities in SK-Hep1 cells. Western blot analyses also showed that WKRG treatment caused dose-dependent decreases in MMP-2 and MMP-9 protein expressions. Moreover, WKRG increased the levels of TIMP-1, TIMP-2, and PAI-1. The present study not only demonstrated that invasion and motility of cancer cells were inhibited by WKRG, but also indicated that such effects were likely associated with the decrease in MMP-2/-9 and uPA expressions of SK-Hep1 cells.